Analysis of Public Services to Bureaucracy Changes in the Covid-19 Pandemic Era - Aas Rohmat; Evi Elisanti (Spirit Publik: Jurnal Administrasi Publik, 2021)
The purpose of study is to analyze public services for employees in Covid-19 Pandemic Era. The research method used is descriptive research with a qualitative approach. This research was conducted at the Directorate of Cooperation, Development, and Internationalization at a University in Solo. Data collection was carried out by observation and documentation. The results shows public services in 2020 with 81 MoUs and 226 MoAs, increasing significantly compared with those 2019 with 79 MoUs, 208 MoAs, and those up to May 2021 with 30 MoUs and 106 MoAs. The number of recommendation/approval processes for the foreign official travel documents for Lecturers & Educators and Students decreases significantly for three consecutive years from 2019 to 2020. The changes in the Covid-19 Pandemic Era are aspects affecting the changes in institutions and work systems. Optimizing the cooperation service system, the Directorate of Cooperation, Development, and Internationalization has created an integrated cooperation information system. The work system in cooperation services changes from the manual or conventional face-to-face one before covid-19 pandemic into an electronic system based on online zoom, google meetings and so on with optimal use of communication technology so ideas are needed new quality and innovative ASN human resources in the pandemic era.